PENGARUH KUALITAS PRODUK DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PADA PT CITRA MANDIRI DISTRIBUSINDO - Junaidi, Junaidi (SCIENTIA JOURNAL, 2021)
decisions at PT Citra Mandiri Distribusindo. The analysis data technique used is the multiple linear method. The operation research design used is descriptive analysis. In this study, the test consisted of validity, reliability, classical assumption test, rnultiple regression analysis, coefficient of determination, t-test and f-test. Sampling has been developed through purposive sampling, consisting of 110 respondents. Data has been collected with the main instrument of the questionnaire. Based on the test results through multiple regression analysis shows that product quality has an effect on purchasing decisions of 40.7% and brand trust has an effect of 58.1% on purchasing decisions. The coefficient of determination has an analysis for R2 of 57.4% while the remaining 24.6% is influenced by other variables. The results of the study indicate that there is a positive and significant effect on product quality on purchasing decisions, there is a positive influence of brand trust on purchasing decisions and a positive and significant effect partially or simultaneously on purchasing decisions at PT Citra Mandiri Distribusindo.